Functionalizing cell-mimetic giant vesicles with encapsulated bacterial biosensors - Trantidou,T; Dekker,L; Polizzi,K; Ces,O; Elani,Y (Interface Focus, 2018)
The design of vesicle microsystems as artificial cells (bottom-up synthetic biology) has traditionally relied on the incorporation of molecular components to impart functionality. These cell mimics have reduced capabilities compared with their engineered biological counterparts (top-down synthetic biology), as they lack the powerful metabolic and regulatory pathways associated with living systems. There is increasing scope for using whole intact cellular components as functional modules within artificial cells, as a route to increase the capabilities of artificial cells. In this feasibility study, we design and embed genetically engineered microbes (Escherichia coli) in a vesicle-based cell mimic and use them as biosensing modules for real-time monitoring of lactate in the external environment. Using this conceptual framework, the functionality of other microbial devices can be conferred into vesicle microsystems in the future, bridging the gap between bottom-up and top-down synthetic biology.